The Impact of Turnover Intention, Work Motivation, and Organizational Culture on Employee Performance in a Construction Service Company - Tri Meliyanti tri (Institut Bisnis dan Ekonomi Indonesia, 2025)
This study aims to examine and analyze the influence of turnover intention, work motivation, and organizational culture on employee performance at a construction service company in Sanggau, West Kalimantan. The research employed a descriptive method with a quantitative approach. From a population of 219 employees, a sample of 69 was selected based on predetermined criteria. Data analysis techniques included validity and reliability tests, normality test, multicollinearity test, heteroscedasticity test, descriptive statistics, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The multiple regression analysis produced the equation: Y = 12.797 + 0.122X₁ + 0.166X₂ + 0.344X₃. The t-test results showed that turnover intention (t = 1.116 < t-table = 1.997) and work motivation (t = 1.207 < t-table = 1.997) did not significantly affect employee performance. However, organizational culture had a significant effect (t = 2.565 > t-table = 2.019). The F-test result showed F = 6.660 > F-table = 2.75 with a significance value of 0.001 < 0.05, indicating that turnover intention, work motivation, and organizational culture jointly have a significant positive effect on employee performance. These findings highlight the importance of organizational culture in enhancing employee performance